Ruolo dell'Infermiere di Famiglia e di Comunità nell'assistenza dei pazienti in dialisi domiciliare e possibili effetti sugli outcome assistenziali - Francesco Burrai; Margherita Gambella; Valentina Micheluzzi (AboutScience Srl, 2022)
From the analysis of the national and international literature and considering the socio-demographic changes, it is necessary to rethink the organizational models capable of giving concrete answers to the new health and welfare needs of the population. The progressive increase of the elderly population and of people with at least one chronic disease and the SARS-CoV-2 pandemic have highlighted the need for a health and social system close to the population, which increases the territorial assistance, in particular at the patient's home. Home care must become an elective place for prevention and health promotion activities. PNRR funds for proximity networks, telemedicine and innovation in the health field will enable assistance to be directed towards a new organizational and operational perspective, where the family and community nurse will play a key role. In the care of patients on home dialysis the evidence described in the literature reports the benefits of home hemodialysis treatment, in which the nurse of the family and community through his care skills, technical and psychological counselling, tele assistance and e-health can be integrated into the home care path, assisting the patient and the family unit and supporting them in the different health needs, especially in the quality of life outcome.